Volume 1: Aircraft Engine; Fans and Blowers; Marine 2016
DOI: 10.1115/gt2016-56960
|View full text |Cite
|
Sign up to set email alerts
|

A Criterion for the Preliminary Design of High-Efficiency Tube-Axial Fans

Abstract: Tube-axial fans are widely used in industrial applications because of their compactness, simplicity, and low cost. However, the achievable fan pressure rise is generally penalised by the absence of a straightener and diffuser, and the consequent waste of tangential and axial dynamic pressures at the fan outlet. The corresponding fan efficiency drop might not comply with stringent regulations like the European Directive for energy-related products. Thus, operation ranges of high efficiency need to be clearly de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
2
6
0
Order By: Relevance
“…Optimal Vortex Distribution Design Method axial velocity, and hence reduced hydraulic losses. A similar conclusion has been reported by Masi et al [124]. By reducing the axial velocity, it is expected that η ts.max increases due to decreased exit losses (dynamic pressure).…”
Section: Overview Of Cfd Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Optimal Vortex Distribution Design Method axial velocity, and hence reduced hydraulic losses. A similar conclusion has been reported by Masi et al [124]. By reducing the axial velocity, it is expected that η ts.max increases due to decreased exit losses (dynamic pressure).…”
Section: Overview Of Cfd Resultssupporting
confidence: 87%
“…Masi and Lazzaretto [123] in 2019 described design approach, integrating design ideas reported by Wallis et al [21,121] and Vad [122] for design of axial fans with high total-to-total efficiency η tt , where a mean-line model, described in Ref. [124], was applied to estimate the η tt of axial fans having constant swirl blade loading. The results showed that the design method permits to obtain increased performance with respect to η tt , but the low Reynolds number due to the fan's small size limited the improvement.…”
Section: Inverse Design Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [3],the authors proposed several analytical formulas and charts to calculate the efficiency of different axial fan configurations on a tube. Matai et al [2] proposed quite a few design parameters to evaluate the performance of an axial fan using Computational Fluid Dynamics CFD techniques.…”
Section: Introductionmentioning
confidence: 99%